48. CHARACTERISTICS OF MALE STERILIZATION PATIENTS WITH VASECTOMY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics of male sterilization patients by vasectomy at Hanoi Obstetrics and Gynecology Hospital.Methods: Cross-sectional descriptive study of 32 patients who underwent vasectomy at Hanoi Obstetrics and Gynecology Hospital from January 1, 2023 to December 31, 2023.Results: The typical characteristics of vasectomy patients were men who had enough children (96,87%), in the age group of 31-45 (84,36%), with a college degree or higher (65,63%) and an above-average income (71,87%). Regarding the patients' partners, the typical group belonged to the age group of 31-45 and with a college degree or higher. The main reason patients chose the procedure was that vasectomy is a permanent and highly secure method of contraception (65,63%). During the procedure, the success rate was 96,87% and the average rating was 4,125/5 .Conclusion: The typical characteristics of the procedure subjects were men with children, middle age, high education level and income. The procedure has a success rate of 96,87% and the average patient rating was 4,125/5 .
Keywords: male sterilization; vasectomy; characteristics